Evaluation of wheat cultivars in two ecological regions of the state of São Paulo - Felicio, João Carlos; Camargo, Carlos Eduardo de Oliveira; Pedro Junior, Mario José; Ferreira Filho, Antonio Wilson Penteado (Pesquisa Agropecuaria Brasileira, 1992)
The characterization of regions to grow wheat in the State of São Paulo, Brazil, with irrigation and without irrigation (upland) conditions was based on water availability for wheat production in the period 1984-89. It has used grain yield data of the cultivars Anahuac, IAC 24 and IAC 162 from trials carried out on limed soils at Maracaí and São José das Laranjeiras in Paranapanema Valley (West region, upland conditions) and at Colômbia and Guaíra (North region, with irrigation). Besides, grain yield and the reaction lo leaf rust, leaf spots and mildew causal agents were evaluated. The water availability for each ten-day period during the crop cycle showed differences between the two regions in relation to rainfall. Irrigation produced a 79% increase in grain yield. The rainfall excess was unfavorable to increase the grain yield in upland conditions, because it allowed a high incidence of diseases caused by fungus. The hibernal water deficiency in the North region was favorable to the irrigation, for it allowed a better distribution of water during the crop cycle. The evaluated cultivars showed susceptibility to leaf spots (Helminthosporium sp.), but the IAC24 cultivar presented resistance to mildew and the most susceptibility to leaf rust among the studied cultivars.
Keywords: wheat crop; water availability; grain yield; diseases